Marking the fishing territory through flags - Mumbai Archive Project Team (Jio Institute, 2024)
Flags and brightly coloured floats mark the fishing area. The size and type of net may vary depending on the boat size and the crew’s hauling capacity. Most fishermen operate small boats, which can accommodate a maximum of two or three people. These boats typically place four to five nets in one area.